The Influence of Education and Business Experience on MSME Financial Literacy in Dolok Masihul District, Mediated by Income - ade Gunawan; Putri Dinda Salsabila (CERED Indonesia Institute, 2026)
Financial literacy plays an essential role in improving the sustainability and competitiveness of Micro, Small, and Medium Enterprises. Limited financial literacy constrains entrepreneurs in managing business finances, accessing formal financial institutions, preparing business plans, and making appropriate investment decisions. This study aims to examine the influence of education and business experience on MSMEs' financial literacy with income serving as a mediating variable among MSME owners in Dolok Masihul District, Serdang Bedagai Regency. The study employed a quantitative explanatory research approach. Data were collected through questionnaires distributed to MSME owners and analyzed using Structural Equation Modeling–Partial Least Squares. The findings indicate that education has a positive and significant effect on financial literacy and income. Business experience also has a positive and significant influence on both income and financial literacy. Furthermore, income positively affects financial literacy and mediates the relationship between education and financial literacy as well as business experience and financial literacy.